Actor and Institutional Dynamics in the Development of Multi-Stakeholder Initiatives - Zeyen, Anica; Beckmann, Markus; Wolters, Stella (Journal of Business Ethics, 2016)
As forms of private self-regulation, multi-stakeholder initiatives (MSIs) have emerged as an important empirical phenomenon in global governance processes. At the same time, MSIs are also theoretically intriguing because of their inherent double nature. On the one hand, MSIs spell out CSR standards that define norms for corporate behavior. On the other hand, MSIs are also the resultof corporate and stakeholder behavior. We combine the perspectives of institutional theory and club theory to conceptualize this double nature of MSIs. Based on a stage model that looks at the interplay of actor and institutional dynamics, we generate insights into why actors join a voluntary MSI, how the various motivations and intentions of the actors influence the standard development, and how these as well as the MSI design are subsequently influenced by both external (institutional) and internal (club) dynamic
UnivIS-Import:2015-10-26:Pub.2014.rw.fbwiwi.LGWSU.actora
Keywords: Business self-regulation; Club theory; Global governance; Institutional entrepreneurship; Institutional theory; Management of diverse interests; Multi-stakeholder initiatives; Political role of the firm; Soft law